Analisis Neraca Air Sungai Tondano dan Optimalisasi Pemanfaatannya - Susilo, Dewi M. M.; Sumarauw, Jeffry S. F.; Hendratta, Liany Amelia (JURNAL ILMIAH MEDIA ENGINEERING, 2017)
Water is an essential natural resource, much needed by humans and other living beings.It is transformed through the hydrological cycle. As a hydrological system, the Tondano River receives input in the form of rainfall and then processes it according to its characteristics into flow. The infiltrated water will rise again by the capillary force, moving horizontally as an interflow or vertically percolating to the aquifer layer that also flows as the baseflow. Water which is not restrained at ground level and also not infiltrated will become overland flow. In the end these three streams will enter the river as a stream / river flow. Thus the river is a joint point between overlandfl ow, interfl ow, basefl ow and rainwater that directly fall on the river body.               In line with the increasing number of population and the development of economy and industry, there is also increasing demand for water for various purposes (mainly for domestic, urban and industrial, irrigation, electricity, tourism and environment). On the other hand, the availability of water is still fixed so that the conflict of interest in water consumption has begun. This situation if allowed to drag on will interfere with people's life and national development in general. To anticipate this, it is necessary to manage water distribution at river level or even between river areas, comprehensively and integrated. Given the complexity of this water allocation system, the assistance of a computer model for water allocation, which is not only used in the planning stage, but also operationalally to assist water managers as a decision support system.                Water balance analysis is a part of water resource development activities, while water balance is a general description of the condition of water availability and its allocation in an area in the last 10 years. Water balance analysis is useful in the prevention of drought in the dry season.       Tondano river basin consists of several rivers. This study aims to determine the amount of water availability and water demand and optimization of its utilization in the river tondano            Optimization and water allocation in this study using secondary data in the form of debit mainstay and wide catchment area with software DSS ribasim            Results revealed that: - total water demand in Tondano River 1.38 m³ /sec.; total water availability in Tondano River is 0.93 m³ / sec.; The need for water and its allocation is for Irrigation Area, PLTA, PDAM.;Irrigation area is 100% fulfilled for DI Noongan, DI Kulo, DI Kinidow, IN Doud Sukur and DI Ranoweleng.; Hydroplasses of 774% of old tonsea, PLTA Tanggari 1 of 61.2%, PLTA Tanggari 2 by 47%.; PDAM Tondano at 100% availability, Manado PDAM at 100% availability. Keywords: water Balance, Tondano river , DSS ribasim, water availability, water demand